Ultrasound signal processing and imaging - Phyoe, Kyaw Kyaw. (2010)
Reverberation and multi-path reflection artifacts are common problems in ultrasound imaging. In this study, the low image quality problem of medical ultrasound imaging in the term of reverberation artifact is addressed, and subsequently a model based on which the reduction technique of reverberation artifacts is proposed. Reverberation caused by reflections of ultrasound signal between two interfaces gives rise to multiple copies of the anatomy at the interface, significantly degrading image quality and accuracy. This study is an extension of the method for the identification of reverberation echoes in multilayered media, based on the comparison of their power spectra (estimated via Fast Fourier Transform) through a least mean square approach, and linear combination of the temporal relationship (based on time-of-flight). To provide a systematic approach, the author investigated the nature of reverberation artifacts formation, and proposed a mathematical model to express reverberations concisely and accurately.